2005
DOI: 10.1158/1055-9965.epi-04-0277
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Variability in Arsenic Methylation in a U.S. Population

Abstract: Several recent investigations have reported associations between a reduced capacity to fully methylate inorganic arsenic and increased susceptibility to arsenic-caused cancer. In these studies, methylation patterns were based on a single assessment of urinary arsenic metabolites collected at the time of cancer diagnosis. However, the latency of arsenic-caused cancer may be several decades, and the extent to which a recent measurement can be used to estimate a person's past methylation pattern is unknown. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 57 publications
3
43
6
Order By: Relevance
“…Several studies have indicated that the proportion of MMA in urine is positively associated whereas the proportion of DMA is inversely associated with the risk of skin and bladder cancer (7)(8)(9). Several smaller studies have indicated that arsenic metabolic process is influenced by demographic (sex and age) characteristics (13,32,33). The present study of arsenic-related skin lesions confirms these inferences in arsenic toxicity.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have indicated that the proportion of MMA in urine is positively associated whereas the proportion of DMA is inversely associated with the risk of skin and bladder cancer (7)(8)(9). Several smaller studies have indicated that arsenic metabolic process is influenced by demographic (sex and age) characteristics (13,32,33). The present study of arsenic-related skin lesions confirms these inferences in arsenic toxicity.…”
Section: Discussionsupporting
confidence: 78%
“…These profiles are good markers reflecting the metabolism of InAs ingested from drinking water [25,26]. The study showed that urinary arsenic methylation indices were fairly stable for 8-10 months for subjects who drank water with a 20 lg/l arsenic level [36]. Subjects that discontinued drinking high arsenic-containing water and changed to consuming low-level arsenic-containing water sequentially had a decreased urinary %MMA V and an increased %DMA V [37].…”
Section: Discussionmentioning
confidence: 89%
“…The relative risks should be interpreted cautiously due to the low incidence of cases of UC, resulting in inadequate statistical power. The arsenic methylation profiles were found to be constant over time, reflecting a uniform exposure via drinking water [54]. Reports about whether the arsenic methylation profile has or does not have long-term consistency are lacking.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An individual's methylation capacity plays an important role in determining the susceptibility to the adverse health effects of arsenic, especially MMA% or the MMA/DMA ratio and arsenic-related skin cancer and bladder cancer [11,12] . A recent report indicated that individual methylation patterns remain fairly stable over time [45] , suggesting that the predominant factors controlling this process are either genetically influenced or related to environmental factors such as long-term dietary patterns or smoking habits that also remain stable over time. Several studies have shown that inherited genetic traits might play important roles in determining individual arsenic methylation capabilities [46,47] .…”
Section: Discussionmentioning
confidence: 99%